STATE EDUCATIONAL POLICY, ADMINISTRATION AND REGYLATION OF EDUCATION SECTOR AS THE SUBJECT OF SUENTIFIC ANALYSIS - Бех, В. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The author analyzes and delimits the notions “state education policy”, “state regulation” and “education management”. The specificity ofcontent and implementation mechanisms of each kind of the organization activity is specified. The information and analytical support ofeach body of organization effect on the national system of education is investigated.